Raising Healthy Children: Age Two - Jamie C. Stolarz; Karla P. Shelnutt (EDIS)
FCS8889, a 4-page illustrated fact sheet by Jamie C. Stolarz and Karla P. Shelnutt, provides general guidelines for parents of two-year old’s in nutrition, physical activity, and language and social development. Published by the UF Department of Family Youth and Community Sciences, January 2010.